Glycated haemoglobin as a dual biomarker Association between HbA1c and dyslipidemia in type 2 diabetic patients - Hammed, Ikhlas K.; Abed, Baydaa A.; Rashid, Nada F. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Diabetic patients with accompanied dyslipidemia are soft targets for cardiovascular diseases. An early intervention to normalize circulating lipids has been shown to reducecardiovascular complications and mortality. Glycated hemoglobin (HbA1c) is a routinely used marker for long-term glycemic control.Objective: to investigate the role of HbA1c as a marker of circulating lipids in type 2 diabetic patientsSubjects and Methods: A total of 450 type 2 diabetic patients (214 males and 236 females), mean age was 55.5 ± 9.35. who attended the National Diabetic Center, Al-Mustansiria university during the period from December 2010 to May 2011 were included in this study Fasting venous blood samples were collected from all the subjects. .HbA1c was estimated by high performance liquid chromatography The Serum was used for analyzing Fasting Blood Glucose (FBG), Total cholesterol (TC),HDL-cholesterol(HDL-C), Triglycerides(TG). Dyslipidemia was defined as per the National Cholesterol Education Program (NCEP) Adult Treatment Panel (ATP) III guidelines. Diabetes was defined as per American diabetes association criteria. The statistical analysis was done by SPSS statistical package version 17.Results: Statistically significant positive correlation was observed between HbA1C and Total Cholesterol (P=0.000), LDL-C (P=0.000), LDL-C/HDL-C ratio (P=0.001), Non-HDL-C (P=0.000)and Risk ratio (P=0.000). The correlation of HbA1c with triglycerides (TG) was positive and statistically significant (P=0.033). Patients with HbA1c value > 7.0 had significantly higher value ofTC, TG, LDL-C, LDL-C/HDL-C ratio, non-HDL-C and risk ratio ( TC/HDL-C) as compared to the patients with HbA1c ≤ 7.0%. However, there was no significant difference in value of HDL-Cbetween the two groups.Conclusion: HbA1c can be used as a potential biomarker for predicting dyslipidemia in type 2 diabetic patients in addition to glycemic control hence early diagnosis can be accomplished through relatively inexpensive blood testing.